STEM-E: Fostering mathematical creative thinking ability in the 21st Century. Issue 1 (May 2021) - Suherman,; Vidákovich, T; Komarudin,
Abstract: Creative thinking is important in improving the formation and discovery of learning ideas in the 21 st century. This study aims to determine differences in the ability of students' mathematical creative thinking in learning STEM and Ethnomathematics (STEM-E). This research employed the experimental design with a simple random sampling technique to determine the sample. The population of this study was 300 junior high school students in Lampung Province, Indonesia. The data collecting technique used was a test instrument tested to see the improvement of mathematical creative thinking. Hypothetical testing used was one-way ANOVA with a significance level of 5%. We found that the average score of the class that applied the STEM-E learning model was 74.71, which is higher, compared to the STEM class with the average score of 72.10, and the control class with the average score of 67.88. It can be concluded that the STEM-E model can be used as an alternative solution for learning in the industrial era 4.0.